Infrared and visible fourier-transform spectra of sulfuric-acid-water aerosols at 230 and 294 K. - Heathfield, A; Newnham, D; Ballard, J; Grainger, R; Lambert, A (1999)
The extinction spectra of aqueous sulfuric acid aerosols fully covering the mid-IR to visible regions from 750 to 23,000 cm(-1) (13.9-0.4 microm) have been measured in the laboratory with a Fourier-transform spectrometer. Both large and small aerosol particles with compositions of approximately 60-70-wt. % H(2)SO(4) were generated and their spectra recorded at 230 and 294 K. The spectra were fitted to a model incorporating room-temperature refractive-index data [Appl. Opt. 14, 208 (1975)] and Mie theory calculations to characterize the composition and size distributions of the aerosol samples.